Discrimination of Zicao Samples Based on DNA Barcoding and HPTLC Fingerprints, and Identification of (22E)-Ergosta-4,6,8(14),22-tetraen-3-one As a Marker Compound - Kretschmer, Nadine; Durchschein, Christin; Heubl, Guenther; Pferschy-Wenzig, Eva-Maria; Kunert, Olaf; Bauer, Rudolf (Planta Medica, 2022)
The unambiguous identification of plant material is a prerequisite of rational phytotherapy. Misidentification can even cause serious health problems, as in the case of the Chinese medicinal herb Zicao. Commercial material labelled “Zicao” may be derived from the roots of Arnebia euchroma (ruan zicao), Lithospermum erythrorhizon (ying zicao), or Onosma paniculata (dian zicao). All of these roots contain shikonin derivatives as main bioactive constituents, but ying zicao and dian zicao contain also hepatotoxic pyrrolizidine alkaloids in high amounts. Therefore, the use of A. euchroma with a very low pyrrolizidine alkaloid content is desirable. Confusions of the species occur quite often, indicating an urgent need for an unambiguous identification method. Discrimination of 23 zicao samples has been achieved by analyses of the nuclear internal transcribed spacer ITS2 and trnL-F intergenic spacer of the chloroplast DNA. Data were analyzed using Bioedit, ClustalX, Mega 11 and BLAST. Results indicate that ITS2 barcoding can accurately distinguish Arnebia euchroma from their adulterants. Subsequently, an HPTLC method has been developed allowing a chemical discrimination of the most widely used species. (22E)-Ergosta-4,6,8(14),22-tetraen-3-one has been identified as characteristic marker compound, allowing an unambiguous discrimination of A. euchroma and L. erythrorhizon.
Keywords: Zicao; Arnebia euchroma; Lithospermum erythrorhizon; Onosma paniculata; Boraginaceae; ITS2; trnL-F; HPTLC; (22E)-ergosta-4,6,8(14),22-tetraen-3-one